The effects of vertical trunk supportability improvement on one-leg rebound jump efficiency. - Kinoshita Kazuaki; Kazunari Ishida; Masashi Hashimoto; Hidetoshi Nakao; Yuichiro Nishizawa; Nao Shibanuma; Masahiro Kurosaka; Shingo Otsuki (PLoS ONE, 2022)
The purpose of this study was to examine the effects of vertical trunk supportability improvement on activities. The study participants were 36 people. Trunk function and physical performance were evaluated using the following tests: trunk righting test (TRT), maximal isometric knee extensor strength test, side hop test, triple hop distance test, stabilometry of one-leg standing, and one-leg rebound jump. The measurement was performed three times: pre-trunk training (pre), post-trunk training for 1 month (post), and 2 months after the second measurement (detraining). Details of trunk training: Two sets of 30-s maximal lateral reach exercises on each side, following the four sets of 15-s maximal raising trunk exercises on each side. The results with TRT in post-training were significantly larger than those in pre-and detraining. Similarly, the results with one-leg rebound jump efficiency in post-training were significantly larger than those in pre-and detraining. Our findings indicate that jump efficiency changes in proportion to the change in vertical trunk supportability.